Active bilingualism delays the onset of mild cognitive impairment. (September 2020) - Calabria, Marco; Hernández, Mireia; Cattaneo, Gabriele; Suades, Anna; Serra, Mariona; Juncadella, Montserrat; Reñé, Ramón; Sala, Isabel; Lleó, Alberto; Ortiz-Gil, Jordi; Ugas, Lidia; Ávila, Asunción; et al.
Abstract: Lifelong bilingualism may contribute to cognitive reserve (CR) in neurodegenerative diseases as shown by a delay of the age at symptom onset in bilinguals with Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI). However, some studies have failed to show this bilingual advantage, suggesting that it might depend on the type and degree of bilingualism. In the present study, we tested the hypothesis that active bilingualism, defined as the continuous use of the two languages as opposed to second language exposition only, may protect against cognitive decline. Moreover, we investigated whether bilingualism as a CR factor may be explained by an advantage within the executive control (EC) system. To do so, we collected clinical measures (age at onset of cognitive symptoms, age at the first medical visit for cognitive impairments, and age at diagnosis) in patients with MCI and patients with AD with different degrees of language experience and usage of Catalan and Spanish. Additionally, all participants were tested on four EC tasks and one long-term memory recognition task. First, results from multiple regression analyses showed that active bilingualism was a significant predictor of delay in the age at onset for all the clinical measures in MCI, but not AD patients. Second, the effect of active bilingualism was independent of occupation, educational level and job attainment across the individuals' lifespan. Finally, although we did not find an effect of active bilingualism across all EC tasks, we did find an effect for conflict resolution. These results are discussed in the context of CR hypotheses, suggesting that compensatory mechanisms may play a role in protecting against cognitive decline. Highlights: We tested whether active bilingualism may protect against cognitive decline. We tested patients with different degrees of language experience and usage. We collected clinical measures and performance in executive control tasks. Active bilingualism was a predictor of delay in the age at onset only in MCI.